Impact of lithium on radioactive iodine therapy for hyperthyroidism - Lingudu, Brahmanandam (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: Radioactive Iodine (RAI) is a common therapy for hyperthyroidism. However hyperthyroidism recurs or persists in 15-18% of patients after RAI. Studies report variable percentage of failure after RAI therapy depending on several variables including I(131). Lithium enhances efficacy of treatment by increasing RAI retention in the thyroid. AIMS: To evaluate the efficacy of Lithium to RAI therapy in terms of cure, reduction of mean thyroid volume, and its safety. SETTINGS AND DESIGN: A prospective comparative study. SUBJECTS AND METHODS: Forty hyperthyroid patients were assigned to two groups, RAI alone and RAI plus lithium and followed for 1 year. Lithium was given in a dose of 900 mg/day in three divided doses for 6 days starting on the day of RAI therapy. Total T3, total T4, and thyroid-stimulating hormone (TSH) were done at baseline, 2,4,6,9, and 12 months. Ultrasound of thyroid was done at baseline and at the end of 1 year. Monitoring was done for side effects of lithium and RAI therapy. STATISTICAL ANALYSIS: Cure rate and time to cure were assessed by Chi-square test. Mean change in thyroid volume was compared by student's t-test. P < 0.05 was considered significant. RESULTS: RAI combined with lithium had a trend towards better cure rate (90%) compared to RAI alone (70%) (P 0.11). Mean time taken to cure was 4.69 months in RAI plus lithium and 7.12 months in RAI alone (P 0.001). Mean change in thyroid volume was similar in both the groups (P = 0.75). There were no side effects of Lithium or RAI. CONCLUSIONS: RAI therapy combined with lithium showed a trend towards higher cure rate, safe and time to cure was less than RAI alone. Hence RAI combined with lithium is a better option in the management of hyperthyroidism than RAI alone.